Survey Perilaku Aktifitas Fisik Lansia Berdasarkan Theory of Planned Behavior di Panti Jompo Minaula Ranooha - Hartati Bahar; Nadya Nababan; Sabrina Nurul; Intan Anggraeni; Rafi Alfarizi; Anti Aprilia (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Physical activity constitutes an essential component of healthy aging, particularly for older adults residing in nursing homes, as they are more susceptible to physical deterioration and limited social interaction. The purpose of this study was to provide an overview of physical activity behavior among elderly residents of Minaula Ranooha Nursing Home, Kendari City, in 2026 by applying the Theory of Planned Behavior (TPB) proposed by Ajzen. This research utilized a quantitative descriptive method with a cross-sectional design. The study involved 30 respondents selected through total sampling from a total population of 35 elderly residents. Data collection was conducted using a structured questionnaire designed to assess the four TPB dimensions, namely attitude, subjective norm, perceived behavioral control, and behavioral intention, measured on a five-point Likert scale. Descriptive statistical analysis was performed using frequencies and percentages. The findings revealed that most participants were between 60 and 69 years old (53.3%) and male (56.7%). In addition, a large proportion of respondents demonstrated favorable attitudes toward physical activity (70.0%), positive subjective norms (80.0%), positive perceived behavioral control (66.7%), and strong intentions to participate in physical activity (86.7%). These results indicate that the three principal TPB constructs contribute collectively to the development of strong intentions to engage in regular physical activity among elderly individuals. Furthermore, nursing home-based programs appear to have an important influence on fostering supportive social environments and positive perceptions related to physical activity. Therefore, continuous implementation of structured physical activity initiatives accompanied by social encouragement is necessary to sustain and improve healthy.